Otoritas Jasa Keuangan Dalam Melindungi Nasabah Perbankan (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The study of the role of the Financial Services Authority (OJK) in protecting banking customers is an important topic in the context of consumer protection and the stability of the financial system. OJK has the authority to end operational supervision procedures related to bank and non-bank exchange transactions, as well as providing legal certainty for customers. It is an Islamic economic perspective, OJK also has a role in protecting sharia banking customers. Legal protection for depositing customers has been regulated in various laws and regulations, including Law Number 21 of 2011 concerning OJK. OJK also has an important role in resolving consumer complaints in accordance with those regulated in the Consumer Protection Law. In addition, OJK is also involved in regulating national economic stimulus policies that have an impact on the spread of COVID-19. Through regulations such as OJK Regulation No. 48/POJK.03 Year 2020, OJK plays a role in loving the guarantee for financial losses felt by depositing customers. Thus, the role of OJK in protecting banking customers is very important in maintaining public trust in the financial system.